The expression of peroxisome proliferator-activated receptor (ppar1 and ppar2) in naive and memory cd4+ t lymphocytes - Mohamed, Rafeezul (2006)
Peripheral CD4+ T cells can be divided into two functional groups based on the expression of distinct isoforms of the surface molecule that contains an intracellular twodomain phosphatase portion, known as CD45. Memory T cells express the lowest molecular weight CD45RO isofonn. whereas naive T cells express CD45RA (human) or CD45RB (mouse) isoforms. CD45 is a protein tyrosine phosphatase which plays an important role in TCR-mediated signaling through its activation of Lck by dephosphorylating the regulatory Tyros. Human naive and memory CD4+ T cells differ in the. requirements for activation and magnitude of the cellular responses. The nuclear receptor, peroxisome proliferator-activated receptor 1 {PPARy) has been reported to be involved in regufatinQ the activities of immune cells such as macrophages or monocytes and T lymphocytes. Given their roles in immune regulation, the current study was carried out to determine the expression of PPARy in human naive and memory CD4+ T cells since it is possible that PPARy may be differentially expressed in the different isoforms of CD45. In addition. the differential signaling patterns and cytokine secretion of these subsets of T cells may require engagement with PPARy isoforms ... a possibility that has not been explored thus far. To further dissect the rote of PPARy in the regulation of naive. and memory CD4+ T cell activation, the PP AR.y agonist, ciglitazone, was used to modulate the activation status of naive and memory CD4+ T cells as wetl as the expression of PPARy itself and selected cytokines. Using Real .. Time PCR. unstimulated naive and memory CD4+ T cells were found not to express PPARy1 and PPARy2, whereas stimulated naive and memory CD4+ T cells express high levels of these receptors with PPARy2 expression being higher than PPARy1 in both cell types (p<0.01). In addition, the PPARy1 expression was higher in stimulated memory as compared to stimulated naive C04+ T cells {p<0.05) whereas there was no significant difference between PPARy2 expression in both types of stimulated cells. The addition- of the PPARy agonist, ciglitazone signifiCantly increased the expression of PPARy1 by about 61-fold and 175-fold in stimulated naive and memory CD4+ T cells respectively (p<0.01). In contrast to PPARy1, the addition of ciglitazone significantly decreased the expression of PPARy2 by about 650-fokl and 140-fold in stimulated na"ive and memory CD4+ T cells respectively {p<0.01). In addition, the expression levels of TGF-)3 and· IL-1 J3 gene were higher in unstimulated naive and memory CD4+ T cells but decreased in their stimulated state (p<0.01). lL-8 gene was expressed at low levels in unstimulated but elevated in stimulated naive and memory CD4+ T cells (p<0.01}. However, there were no significant differences in the levels of these cytokines between naive and memory CD4+ T celts between both states. IL-4 lFNy, IL-5, IL-13, TNFa, GM-CSF and IL-6 were only expressed in stimulated naive and memory CD4+ T ceUs but not. in their unstimulated state. The expression levels of IL-2 and IL-13 were significantly higher in stimulated naive as compared to stimulated memory C04+ T cells (p<0 .. 01 ). In contrast, the expression levels of IFNy were significantly higher in stimulated memory as compared to stimulated naive CD4+ T cells (p<0.05). However, there were no significant differences in the expression of IL-5, IL-6, TNFa and GM..CSF between both stimulated cell types. The addition of ciglitazone. decreased the expression levels of TGFp, IL-1p, IL-8, IL-2, IFNy, IL-5, TNFa. and GM-CSF in stimulated memory and na"ive CD4+ T cell& The induction of PPARr1, and suppression of PPARy2 expression in naTve and memory CD4+ T cells in the p~sence of ciglitazone suggest that the PPARy isoforms may have different functions in T cell regulation. The expreqi~n of $elected cytokine genes inactivated naive and memory CD4+ T cells is consistent with previous studies. The exact mechanism of how PPARy inhibit cytokine expression in stimulated naive and memory CD4+ T cells or which PPARy isoforms is responsible for this effect remain uncertain. It is possible that PPARy inhibit the expression of cytokine genes in these stimulated cell subsets. via interacting with NF-KB, AP-1 and STATs. which is important transcription factors for these cytokines as shown by previous studies in other cells.